Gold Nanoclusters Potentially Facilitate Dentin Regeneration by Functioning Immunomodulation - Yang, Lan; Xiao, Lan; Liu, Tianqing; Gao, Wendong; Xiao, Yin (Frontiers in Materials, 2022)
It is presently difficult to achieve dental pulp vitality maintenance and regeneration in adult teeth. Dentin destruction results in the exposure of the dental pulp tissue to infectious oral environments, thereby triggering continuous severe pulp inflammation that impedes the self-regenerative capacity of the pulp. For these reasons, the regeneration of dentin bridges to block pulp tissue from the oral environment is an indispensable step. Nevertheless, this goal is difficult to achieve using present strategies, because the importance of immunoregulation in the pulp inflammatory microenvironment has been ignored. In our previous study, we found that the nanomaterial dihydrolipoic acid-functionalized gold nanoclusters (DHLA-AuNCs) efficiently regulated inflammatory responses in microglia (resident macrophages in the central nervous system), suggesting that DHLA-AuNCs may induce dentin bridge regeneration by regulating dental pulp macrophage responses. In the present study, we found that DHLA-AuNCs inhibited the M1 phenotype while promoting the M2 phenotype in macrophages in inflammatory conditions in vitro. This regulation of the inflammatory environment in dental pulp enhanced the differentiation of human dental pulp stromal cells (hDPC) toward odontoblasts, a beneficial effect on dentin regeneration. DHLA-AuNCs also had a direct role in the differentiation and mineralization of hDPC. These findings suggest that DHLA-AuNCs facilitate dentin regeneration through both efficient immunomodulation and direct induction of stromal cell differentiation/mineralization, providing a potential therapeutic nanomaterial for dentin bridge regeneration, effects that would be beneficial for dental pulp regeneration.